“mäandernd, ornamentalisch, ohne progression”? Intertextualität in Michael Roes’ Freibeutertext Leeres Viertel (1996) - Schmitt-Maass, Christoph (Revista de Filología Alemana, 2007)
Facing the interferences within post-modern ethno poetic texts and literary tradition, this contribution analyses the intertextual and intercultural items instancing the novel Leeres Viertel [Empty Quarter] (1996) by Michael Roes. Pointing out that Roes alludes on various travel books concerning 19th century Orient, the construction of his novel becomes evident and could be considered old-fashioned and “exotic” character.
Keywords: Intertextuality; Interculturality; Travel report; Enlightenment